2016
DOI: 10.1080/17579961.2016.1250378
|View full text |Cite
|
Sign up to set email alerts
|

Beyond regulatory compression: confronting the liminal spaces of health research regulation

Abstract: Biomedicine and the life sciences continuously rearrange the relationship between culture and biology. In consequence, we increasingly look for a suitable regulatory response to reduce perceived uncertainty and instability. This article examines the full implications of this 'regulatory turn' by drawing on the anthropological concept of liminality. We offer the term 'regulatory compression' to characterise the effects of extant regulatory approaches on health research practices. With its focus on transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The responses to the Delphi survey capture a core, recurrent theme that cuts across the regulation of health regulation, namely uncertainty [29,30]. Uncertainty, of course, can arise in multiple forms in this field; research by its very nature is an uncertain endeavour.…”
Section: Regulatory Uncertaintymentioning
confidence: 99%
See 3 more Smart Citations
“…The responses to the Delphi survey capture a core, recurrent theme that cuts across the regulation of health regulation, namely uncertainty [29,30]. Uncertainty, of course, can arise in multiple forms in this field; research by its very nature is an uncertain endeavour.…”
Section: Regulatory Uncertaintymentioning
confidence: 99%
“…We can thus derive two sub-themes from the responses. First, inefficient legal responses to uncertainty [30] mean that those who fall within the rubric of regulatory rules are often left with various difficulties about how to navigate them. Second, some participants reported that the law is creating uncertainty for various 'partners' in the health research process, especially for researchers.…”
Section: Regulatory Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…This article offers an analysis and a defence of such a model. Put otherwise, it represents a call to adopt a processual approach to regulation and governance (Taylor-Alexander et al 2016). As articulate above, such an approach focusses on the experiences of governing, both for those in such a role and for those subject to governance.…”
Section: Biobanks As a Global Phenomenon And A Challenge To Processuamentioning
confidence: 99%